The level of Anxiety from Coronavirus and its Relationship to the Coping Strategies that used during the Period of Home Quarantine - اسكندر مها (Latakia University Journal -Medical Sciences Series, 2021)
This study aimed to assess the level of anxiety from Corona virus and its relationship to the coping strategies that used during the period of home quarantine. The study was conduct using the Corona Virus Anxiety Scale and the Coping Strategies Questionnaire on a sample of 106 students from the College of Nursing students distributed over the four years. Data collection used the electronic questionnaire method. The results showed that the largest percentage of students had a normal and mild level of anxiety (52.8% -40.6%, respectively). The most used coping strategies are acceptance, cognitive building, and conversion to religion and spirituality, while the less used ones are avoidance, flight, and denial. There was a statistically significant relationship between the level of anxiety and the use of non-adaptive strategies. The study recommends educating university students specially and community in general about the common negative psychological consequences of the Corona epidemic, promoting healthy behaviors, advising people to reduce their exposure to negative news, and directing students to use alternative methods of communication during the Quarantine.